TRANSFORMATION OF SPIRITUAL AND EDUCATIONAL REFORMS IN ENSURING SUSTAINABLE DEVELOPMENT OF UZBEKISTAN (Web of Teachers: Inderscience Research, 2025)
In this article, the implementation of the transformation of spiritual and educational reforms and the strategy of spiritual and educational reforms in ensuring sustainable development of Uzbekistan serves to implement measures in the development of New Uzbekistan, raising the spiritual and educational level of our people, strengthening the material and technical base of cultural and art institutions, comprehensive support of representatives of the sphere. The article also covers the issues of creating qualities in young people, such as loyalty to the motherland, entrepreneurship, willpower, ideological immunity, kindness, responsiveness, tolerance, legal culture, innovative thinking, hard work.